Development and evaluation of wideband negative response in ultra-thin polygon metamaterial - Al Gburi, Ahmed Jamal Abdullah; Sharma, Atipriya; Singh, Harbinder; Gupta, Amit (Springer Science and Business Media Deutschland GmbH, 2024)
In this study, an ultra-thin multi-polygon structure is employed to develop an ultra-thin double-negative (DNG) metamaterial (MM). The developed structure showcases an ultra-wideband Single-Negative (SNG) response, characterised by a minimal thickness of 0.2 mm, within the frequency range of 2–12 GHz. MM parameters reveal distinctive characteristics, including consistently negative permeability identifying it as a Mue Negative (MNG) material. The permittivity displays Epsilon Negative (ENG) traits within specific frequency bands, giving rise to a DNG refractive index within these negative regions. This remarkable adaptability underscores its immense potential for controlling electromagnetic waves, catering to an array of applications. Experimental validation aligns exceptionally well with simulated results, affirming the practical efficacy of this design. The results clearly show the potential of the adopted approach for various MM practical applications. Graphical abstract: (Figure presented.).